GENETICALLY ANALYSIS OF DIFFERENT ECORACES OF TASAR SILK MOTH OF ANTHERAEA SPECIES - Akhilesh Kumar, Akhil Abhishekh and Deepti (International Journal of Advanced Science and Technology, 2020)
Tasar silk is delivered from the tasar silkworms (Insecta: Lepidoptera: Saturniidae) which has numerous ecoraces chiefly constrained by winning ecological conditions. The tasar silkworms are developed ex-situ in regular woodlands, in any case, a few endeavors have been made for its semitraining. Tasar culture is a conventional occupation for lakhs of innate populace in our nation. The present investigation portrays the variety in the various phases of tasar silkworm Antheraea mylitta Drury which is dispersed as ecoraces in changed geological regions. From the examinations it is seen hat rich organic decent variety of Antheraea mylitta Drury principally is because of its wide scope of issemination, climatic variables, and nourishment plants and so forth. Which have prompted varieties in their ethology and physiology. The various strains of the tasar silkworm, Antheraea mylitta were examined utilizing the straightforward grouping rehash tied down polymerase chainresponse (SSR and ISSR - tied down PCR).